SUPLEMENTATION OF VIRGIN COCONUT OIL (VCO) PRODUCTS WITH INTARAN (Azadirachta indica) LEAF EXTRACT IN INHIBITING THE GROWTH OF ACNE BACTERIA Propianibacterium acnes - I Wayan Karta; Burhannuddin Burhannuddin (Balai Besar Penelitian dan Pengembangan Pascapanen Pertanian, 2021)
The dangers of resistance to Propionibacterium acnes and the high cost of treatment prompted the discovery of medicinal sources from natural substances that could act as antibacterials. One of them is using post-harvest coconut products in the form of virgin coconut oil (VCO) with extract of intaran leaves (Azadirachta indica). The purpose of this study was to determine the phytochemical characteristics, inhibition zone and their categorization and to study the difference or effect of VCO supplemented with extracts of intaran leaves (Azadirachta indica) with various concentrations on the growth of Propionibacterium acnes. This study used a posttestonly control group design. The VCO mixed with extracts of intaran leaves with various concentrations of 5%, 10%, 15%, 20% and 25%. The antibacterial test was carried out using the Kirby-Bauer disc diffusion method. Data analysis used the Kruskall Wallis and Mann Whitney test. The VCO mixture supplemented with extracts of intaran leaves showed the presence of tannins, flavonoids, terpenoids, saponins, and alkaloids. The mean diameter of the inhibition zone of virgin coconut oil (VCO) supplemented with leaf extract at a concentration of 5%, 10%, 15%, 20% and 25% of the growth of P. acnes is 9.4 mm; 18.3 mm; 9.9 mm; 12.6 mm; and 9.9 mm. Data analysis showed that there were differences and the effect of adding extracts to the resulting inhibition zone diameter. The concentrations of leaf extract of 5%, 15%, and 25% were classified as moderate, while the concentrations of 10% and 20% of leaf extract were classified as strong. The 10% concentration had the highest inhibition zone diameter in inhibiting the growth of P. acnes. This combination has the potential to treat acne and needs to be carried out in vivo research.